Mechanical Properties of Surface-Charged Poly(Methyl Methacrylate) as Denture Resins - Sang E. Park; Maggie Chao; P. A. Raj (International Journal of Dentistry)
The aim of this study was to examine the mechanical properties of a new surface-modified denture resin for its suitability as denture base material. This experimental resin is made by copolymerization of methacrylic acid (MA) to poly(methyl methacrylate) (PMMA) to produce a negative charge. Four experimental groups consisted of Orthodontic Dental Resin (DENTSPLY Caulk) as a control and three groups of modified PMMA (mPMMA) produced at differing ratios of methacrylic acid (5 : 95, 10 : 90, and 20 : 80 MA : MMA). A 3-point flexural test using the Instron Universal Testing Machine (Instron Corp.) measured force-deflection curves and a complete stress versus strain history to calculate the transverse strength, transverse deflection, flexural strength, and modulus of elasticity. Analysis of Variance and Scheffe Post-test were performed on the data. Resins with increased methacrylic acid content exhibited lower strength values for the measured physical properties. The most significant decrease occurred as the methacrylic acid content was increased to 20% mPMMA. No significant differences at P<.05 were found in all parameters tested between the Control and 5% mPMMA.